Why station areas succeed: analyzing North America’s largest light rail network - Walter, Brennan (Kansas State University, 2023)
Light rail networks represent a substantial public transportation investment in cities. Common planning practice suggests that the construction of these networks will lead to the construction of denser and less car dependent transit-oriented development. While this is true in most places where light rail is constructed, the development benefits are not realized near each station site. This research tests the “build it and they will come” paradigm for TOD near light rail station areas. We used the Dallas Area Rapid Transit (DART) light rail network as an exemplar for findings potentially applicable to other cities and explored it with a mixed-methods approach using interviews with experts and data modelling. Through a trial-and-error process turning on and off variables in the model, we tested planner’s hypothesis and conventional wisdom about where TOD is most likely to succeed.
Keywords: Light rail; Transit-oriented development; Dallas Area Rapid Transit